Nondestructive analysis of jade artifacts from the Cemetery of the Ying State in Henan Province, China using confocal Raman microspectroscopy and portable X‐ray fluorescence spectroscopy. (8th January 2014) - Zhao, H. X.; Li, Q. H.; Liu, S.; Hu, Y. Q.; Gan, F. X.
<x xml:space="preserve">Abstract</x> Confocal Raman microspectroscopy and portable X‐ray fluorescence spectroscopy were used nondestructively to characterise 18 intact jade artifacts from the Cemetery of the Ying State in Pingdingshan, Henan Province, China. These jade artifacts date from the early to the middle of the Western Zhou Period (the mid‐11th to the mid‐9th century BC). Thirteen jade artifacts made of tremolite and two jade artifacts made of actinolite were discriminated from each other by their hydroxyl stretching modes, and a malachite pendant, a muscovite dagger‐axe, and a crystal pendant were also identified. Black graphite was analysed in three jade artifacts composed of tremolite, and the mineralization temperatures were estimated and compared. A red powder was found on the surface of all of the jade artifacts, and this was found to be cinnabar (HgS), which is thought to have been added to the tomb environments during burial ceremonies. The chemical compositions and the possible provenances of the jade artifacts are briefly discussed. Copyright © 2014 John Wiley & Sons, Ltd.